… It's about the Journey!. Issue 12 (December 2014) - Paduraru, A
The aim of this article is to discuss: the importance of effective communication, the importance of maintaining confidentiality and equality for all individuals, the importance of maintaining a secure, safe and hygienic environment within the operating department, the principles of maintaining sterility and controlling infection, and the resulting hazards if these are not maintained. A paediatric patient was followed through her perioperative journey to find out if routinely, at the author's trust, the values of the NHS constitution – the six Cs – are being upheld.